Understanding the behavioral drivers of smallholder agro-ecological practice adoption in Benin and Burkina Faso - Tapsoba, Parfait K.; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; OUEDRAOGO, Alexis; DASSEKPO, Innocent Sègla; Kestemont, Marie-Paule; Kabore Konkobo, Madeleine; Achigan-Dako, Enoch Gbenato (My University, 2023)
The current international context characterized by environment, and socio-political crises, and the related issue of instability of food supply and agricultural inputs, revives the need for agroecological transition of West African smallholders. This study aims to analyze the socio-psychological determinants of the adoption of crop rotation (CR) and cereal-leguminous intercropping (CLI) practices, two popular agroecological practices in Benin and Burkina Faso, in order to provide additional levers for action for the agroecological transition in these two countries. To this end, a stepwise survey involving all the municipalities of Atacora (9) in Benin and Houet (13) in Burkina Faso was conducted among 400 family farmers. The planned behavior model was then used to analyze their intentions and decisions to adopt these practices through structural equation modeling. Findings show that regardless of the practice, farmers' perceived control influences their intention as well as their adoption decision. Similarly, farmers' intention also had a positive and significant effect on their decision to implement these two practices. These results contribute to a better understanding of farmers' decisions process, and therefore offer opportunities to positively influence it.
Keywords: Agroecology; Theory of planned behavior; Intention and decision to adopt; Structural equation modeling; Cereals-leguminous intercropping; Crop rotation